2018
DOI: 10.1097/fbp.0000000000000388
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to opiates in male adolescent rats alters pain perception in the male offspring

Abstract: During the past decades, the use/misuse of opioids has increased dramatically among adolescent population. It is now well acknowledged that various morphological and physiological changes occur in the brain during adolescence. During this critical period, brain development and maturation could be affected by several factors including stress, drug abuse, nutritional status, etc. Although studies on transgenerational effects of substances such as alcohol, nicotine, and cocaine have focused on both paternal and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…We have recently demonstrated in our previous research that morphine administration during adolescence makes transgenerational effect on pain perception in the offspring. By using the same experiment, that is, formalin test, we reported that the duration of interphase significantly decreased in morphine‐sired animals compared to saline‐sired ones (Pachenari, Azizi, Ghasemi, Azadi, & Semnanian, ). The results of long‐term and transgenerational effect of adolescent morphine exposure on pain perception which are described in the current and mentioned studies, respectively, are not exactly the same.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…We have recently demonstrated in our previous research that morphine administration during adolescence makes transgenerational effect on pain perception in the offspring. By using the same experiment, that is, formalin test, we reported that the duration of interphase significantly decreased in morphine‐sired animals compared to saline‐sired ones (Pachenari, Azizi, Ghasemi, Azadi, & Semnanian, ). The results of long‐term and transgenerational effect of adolescent morphine exposure on pain perception which are described in the current and mentioned studies, respectively, are not exactly the same.…”
Section: Discussionmentioning
confidence: 92%
“…The reason we opted for this dose was that, in our previous laboratory study, it was observed that injection of 2.5 mg/kg morphine significantly alters analgesic response of adolescent morphine‐treated animals compared to the saline‐treated counterparts in tail flick test during adulthood (data not published). Moreover, we observed that adolescent morphine exposure made no significant transgenerational effect on analgesic response to 2.5 mg/kg morphine injection in rat model of formalin test (Pachenari et al, ), so we aimed to compare the long‐term and transgenerational effect of morphine analgesia by using formalin test.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its limitations, the formalin test is still currently used in the evaluation of both pain and inflammation in animal models. 76,77 Second, the concentration of curcumin and/or ST in the blood, as well as in the brain tissue, was not quantified. This kind of measurements could bring useful information, but a separate design using different forms of curcumin must be tested.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Therefore, assessing antinociceptive properties of opioids can serve as a proxy for understanding opioid reward. A recent study showed that chronic morphine treatment in Wistar rat sires did not affect morphine-induced antinocieption in the offspring as assessed by the formalin pain test (Pachenari et al, 2018). However, in a separate study, exposure to a single dose of morphine in adult male Sprague Dawley rats prior to breeding resulted in F1 male offspring that exhibited enhanced antinociceptive effects of morphine in the hot plate assay (Cicero et al, 1995).…”
Section: Opioidsmentioning
confidence: 99%